PENGARUH KARAKTERISTIK KUALITATIF LAPORAN KEUANGAN TERHADAP PENGGUNAANNYA DALAM PENGAMBILAN KEPUTUSAN KREDIT BANK UMUM DI BANJARMASIN - Rusmanto Rusmanto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
This research objective is to know the influence of company’s qualitative characteristics of financial statement and its usage for public banks in Banjarmasin to give credit approval. Population in this research are 32 companies which accept credit firm banks with minimum credit amount of Rp. 500.000.000 and with working capital during 2004 to 2005 in 12 banks in Banjarmasin. And the respondents, taken with simple random sampling method, are credit analists or superintendents who are competent in giving a credit decision. And the results indicate that company’s qualitative characteristics of financial statement which are comprehensive (X1), relevant (X2), reliable (X3), and comparative (X4) simultaneously have positive effect (about 64,01%) for public banks in Banjarmasin in considering a credit approval.